Utilization of Technology in MSME Marketing Strategy Through Digital Media - Purbohastuti, Arum Wahyuni; Putri, Solehatin Ika; Pertiwi, Widya Nur Bhakti; Muhammad Johan Widi Kusyanto; Edwin Perdana Adiwijaya, Edwin Perdana Adiwijaya (EQUATOR SINAR AKADEMIA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) increasingly use digital marketing to increase visibility, competitiveness, and turnover. The methods used in this community service include lectures, question and answer, and promotional simulations with social media. This program aims to train MSMEs in using digital technology for marketing. The discussion in this article is the application of digital marketing strategies and it is hoped that this training will have an impact on the skills of MSMEs players so they can carry promotions effectively and efficiently.